Behavioural Intelligence Searching Economic Rent and Capital Maintenance: An Experimental Setting in Bank Interest Rate Opportunities - Sumiyana, Sumiyana; Mussanadah, Atik Ul (Journal of Posthumanism, 2025)
This study investigates people's behaviours in saving and depositing their funds in Islamic Sharia or conventional banks. People would probably switch their savings and deposits from a conventional bank to a Sharia one or vice versa. This research uses a true experiment to examine people’s behaviours regarding savings and deposits in Sharia or conventional banks. In the first stage, the researchers measured the participants’ religiosity and underlying intelligent behaviour regarding capital maintenance. In the second stage, the researchers presented the participants with two designs for fund mutations from Sharia to conventional banks and from conventional to other convents or Sharia banks. This study finds that Sharia’s depositors and savers switch their funds to conventional banks when offering higher interest rates. It also shows that Sharia’s depositors and savers will hold their funds when conventional banks offer the same and lower interest rates. In addition, it explains precisely the same behaviours of conventional banks’ depositors and savers when Sharia ones tender higher interest rates. Therefore, it concludes that religiosity is an enigma construct compared to capital maintenance. Indonesians’ cognitions are universally rooted in their profound faith but behaviourally prioritising economic rent, capital maintenance and prospective expectancy. This research doubts the essential meaning of religiosity reflected by people’s beliefs, attitudes and behaviours whether they face economic rent opportunities. Nevertheless, it reveals that Indonesians are in economic-mental health due to conscientiousness to improve social welfare.